Pengawasan Hukum Terhadap Penyalahgunaan Izin Tinggal Terbatas Penanaman Modal Asing - Kresna Wardana, I Gusti Putu Anom; Putri, Tsaltsa Syah; Laksono, Tunggal Bayu (Jayapangus Press, 2021)
Every country in the world has sovereignty, especially over the security of its country, one of the things that can threaten the security of the country is the entry of foreigners whose activities are not according to the permits given to them, one of which is the misuse of residence permits by foreign investors in Indonesia. This study aims to explain in detail about the misuse of residence permits by a foreign investor in Indonesia and further discusses the legal supervision carried out by Immigration in dealing with irregularities committed by foreigners. This study uses a descriptive type with empirical normative research methods, where in finding data sourced from secondary data, namely through interviews, and secondary data obtained by conducting literature reviews such as laws and other regulations. At this writing it was found that the perpetrators took actions that were not in accordance with the purpose of giving a residence permit and did not carry out proper procedures to obtain a new Limited Stay Permit. From this research, it can be concluded that the supervision of foreigners must be tightened, one of which is the effective and efficient implementation of the Foreigner Supervision Team which is formed on the basis of synergy between related Ministries/Institutions in Indonesia.